Translating Embodied Cognition for Embodied Learning in the Classroom - Macrine, Sheila L.; Fugate, Jennifer M. B. (Frontiers in Education, 2021)
In this perspective piece, we briefly review embodied cognition and embodied learning. We then present a translational research model based on this research to inform teachers, educational psychologists, and practitioners on the benefits of embodied cognition and embodied learning for classroom applications. While many teachers already employ the body in teaching especially in early schooling, many teachers’ understandings of the science and benefits of a sensorimotor engagement or embodied cognition across grades levels and the content areas is little understood. Here, we outline seven goals in our model and four major “action” steps. To address steps 1 and 2, we recap previously published reviews of the experimental evidence of embodied cognition (and embodied learning) research across multiple learning fields, with a focus on how both simple embodied learning activities -as well as those based on more sophisticated technologies of AR, VR, and mixed reality - are being vetted in the classroom. Step 3 of our model outlines how researchers, teachers, policymakers, and designers can work together to help translate this knowledge and work together in support of these goals. In the final step (step 4), we extract generalized, practical embodied learning principles, which can be easily adopted by teachers in the classroom without extensive training. We end with a call for educators and policymakers to use these principles to identify learning objectives and outcomes, as well as track outcomes to assess whether program objectives and competency requirements are met.